Preparation of dahi from cow and buffalo skim milk with addition of mango (Mangifera indica) juice - Biswas, Sawpna Rani; Kibria, Sumya; Habib, Md Rezwanul; Siddiki, Mohammad Shohel Rana; Rashid, Md Harun Ur (Asian Journal of Medical and Biological Research, 2017)
The aim of this research was evaluation of dahi prepared from cow and buffalo skim milk addition of mango juice. Four types of dahi were prepared from cows and buffalos skim milk which designated by A (cows skim milk), B (cows skim milk with 10% mango juice), C (buffalos skim milk) and D (buffalos skim milk with 10% mango juice). The quality of prepared dahi was measured by organoleptic, chemical and microbiological test. Smell and taste, body and consistency, colour and texture score of dahi improved due to adding mango juice to compare with their control group. The overall acceptability score of B and D sample were 85.67±1.53 and 81.67±4.04 which higher than both control group. From chemical analysis, it was found higher total solids in 10% mango juice containing B (202.0±0.20 g/kg) and D (196.0±0.49 g/kg) dahi samples than both control groups. Again, lower fat and protein contents found in 10% mango juice containing B and D dahi samples. Total viable count was found significantly higher in both 10% mango juice containing B and D dahi samples than both control groups. In conclusion, that addition of mango juice with cows skim milk dahi or buffalo skim milk dahi were both better in terms of organoleptic and chemical qualities more acceptable than plain skim milk dahi. Asian J. Med. Biol. Res. June 2017, 3(2): 191-197